Optimalisasi Coverage Area Jaringan WiFi Di SMK N 1 Tegalalang Dengan Menggunakan NetSpot - Yuda I Made Wedana Yuda Yana; Gede Arna Jude Saskara; Ida Bagus Nyoman Pascima (POLITEKNIK NEGERI JAKARTA, 2025)
This study focuses on optimizing the Wi-Fi network coverage area at SMK Negeri 1 Tegalalang through mapping and analysis using the NetSpot application. Stable and evenly distributed internet connectivity is essential to support digital-based learning activities in schools. Preliminary observations revealed several blank spots and uneven signal distribution across classrooms and buildings, indicating the need for improvement in network infrastructure. The research employed an action research approach consisting of four stages: diagnosing, action planning, action taking, and evaluating. Data collection was conducted using both active and passive site surveys, measuring the Received Signal Strength Indicator (RSSI), and generating heatmap visualizations to illustrate signal distribution. The analysis emphasized three main aspects: wall attenuation factors, access point positioning, and potential channel interference that contributed to performance degradation. The findings provide a comprehensive signal coverage map along with recommendations for more strategic placement of access points. These recommendations resulted in improved coverage with a minimum RSSI target of –65 dBm and a service area of at least 80%. The outcomes of this study are expected to serve as a valuable reference for schools in designing and enhancing Wi-Fi infrastructure, ensuring reliable connectivity that supports the implementation of online and blended learning effectively.